Contribution to the bryoflora of Morocco: Toubkal National Park (TNP) Ourika Valley - Fakihani, Abdelhalim; Ouhammou , Ahmed; Loudiki , Mohamed; Douira , Allal (Mediterranean Botany, 2025)
The bryophyte flora of the upper Ourika valley, located to the east of the Toubkal National Park (Morocco), is catalogued. No such studies have been conducted in this valley before. As a result of this study, the catalogue consists of 47 species of mosses. No liverworts or hornworts are encountered. Of these taxa, two (2) are newly reported for Africa (Amphidium mougeotii (Schimp.) Schimp., Pseudoleskeella nervosa (Brid.) Nyholm), one (1) is new for North Africa (Brachythecium mildeanum (Schimp.) Schimp.), one (1) is new for Morocco (Orthotrichum bistratosum (Schiffn.) J. Guerra) and eleven (11) are new for the Toubkal National Park.